Pengaruh penerapan green accounting terhadap nilai perusahaan dengan profitabilitas sebagai variabel moderating pada perusahaan sub sektor tambang batubara yang terdaftar di Bursa Efek Indonesia periode 2019-2021 - Yuliani, Elvina; Prijanto, Budi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
There are still many cases of environmental pollution. One of them is a coal mining company, showing a lack of company awareness regarding the importance of preserving the environment. Companies that pay attention to every aspect of their activities will affect the value of the company. The greater the company's value, the greater its profitability. Green accounting is considered one of the solutions to existing problems. The purpose of this study is to find out and analyze whether the application of green accounting has a significant effect on firm value and whether profitability is able to moderate the relationship between the application of green accounting and firm value. The data used is secondary data. The population of this study are coal mining subsector companies listed on the Indonesia Stock Exchange for the 2019–2021 period. The research sample was determined using a purposive sampling technique, and data was obtained from 12 companies. The analysis technique used moderated regression analysis with the help of SPSS 25 software. The results showed that the application of green accounting had an effect on firm value, but profitability was not able to moderate (weaken) the relationship between the two.